The Soviet Epoch in Polycode Precedent Media Reflection, or From Each According to His Ability, to Each According to His Need - Tatiana V. Marchenko (Актуальные проблемы филологии и педагогической лингвистики, 2024)
The article studies linguasemiotic features and functional meanings of precedent phenomena (PP) of the Soviet past through the prism of polycode representation in modern discursive space. The study is aimed at analyzing Soviet precedents of graphic design, sociocultural life, everyday life and gluttony in mass media communication. During pinpoint sampling of polycode units (Internet memes) from the Russian-language Internet segment, 500 texts that met the criterion of featuring a verbal or visual PP representative with the semantic component “Soviet, relating to the historical period of the USSR” were identified. The analysis of PP that implement media reflection of the cultural and historical heritage of the Soviet epoch was carried out based on semiotic, structural and semantic, intertextual, stylistic and discourse analyses. The features of updating the associative connection between the artistic and aesthetic design of polycode text and socio-cultural signs of the Soviet period have been established. The polycode nature of precedent references to the cinematic and musical heritage of the Soviet period is confirmed by the presence of both verbalized elements (names, titles) and non-verbal (audio fragments, captions and visual images); the discursive PP actualization is presented in reminiscent and allusive formats. Text examples demonstrate the dominance of a visual precedent image, appealing to gluttony perceptions and mediated by the context of the past or the era of the Soviet Union. Two models of encoding PP related to Soviet everyday life have been established: the retrospective one (reliance on visual representatives of archaism and verbal temporality representatives) and the axiological one (the verbal part of the message postulating the high quality of products produced in the USSR; visual elements act as a referential basis appealing to culturally specific precedent base).